Radiation-Induced Left Main Coronary Artery Stenosis in a Patient with Atretic Internal Mammary Arteries - Siddhant Dogra; Asha M. Mahajan; Albert Jung; Michael Attubato; Muhamed Saric; Alan Shah (Case Reports in Cardiology)
Coronary artery disease (CAD) is a known potential complication of thoracic radiation treatment that typically affects the proximal segments of the coronary arteries, requiring coronary artery bypass grafting (CABG). We present a case of acute coronary syndrome occurring in a 57-year-old man with prior thoracic radiation therapy following resection of a chest wall chondrosarcoma. Coronary angiogram demonstrated significant areas of stenosis in the left main coronary artery (LMCA) and ostial left anterior descending (LAD) coronary artery. The patient was also found to have atretic bilateral internal mammary arteries as a consequence of his radiation therapy, rendering them unsuitable as grafts. Percutaneous coronary intervention (PCI) was thus performed with a successful outcome. To our knowledge, this is the first case of radiation-induced CAD of the LMCA with atretic internal mammary arteries treated successfully with PCI.